GERAKAN WOMEN’S MARCH DAN KEBIJAKAN KESETARAAN GENDER DI INDONESIA; REALITY OR CLAIM? - Zaky Ismail (PSGA LP2M IAIN Pontianak, 2020)
This study aims to discuss the effect of Women‟s March on gender equality policies in Indonesia in 2017-2018. This article used descriptive-qualitative method and used interview techniques and literature study that are relevant to this research. After conducting research, it can be seen that Women‟s March is a effort that initiated in Washington D.C. This communal movement not single arisen in Washington D.C. then furthermore ensued in numerous countries. In Indonesia, Women‟s March occured in 2017-2018. In this research, it shows that through the Women‟s March involvement by leading protests, lobbying, and numerous other follow-up actions are intelligent to effect the policy of gender equality in Indonesia during 2017-2018.